2023
DOI: 10.1002/anie.202312131
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Intrapenetrated Hierarchical Zeolites with Highly Complete Framework via Protozeolite Seeding

Yinghao Liu,
Xingxing Wang,
Junyan Li
et al.

Abstract: Creation of intrapenetrated mesopores with open highway from external surface into the interior of zeolite crystals are highly desirable that can significantly improve the molecular transport and active sites accessibility of microporous zeolites to afford enhanced catalytic properties. Here, different from traditional zeolite‐seeded methods that generally produced isolated mesopores in zeolites, nanosized amorphous protozeolites with embryo structure of zeolites were used as seeds for the construction of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These are often referred to as protozeolites or embryonic zeolites ,, since they possess elements of the zeolite structure but are very small in size with only short-range order (a few nanometers in length). Studies have demonstrated that seeding growth mixtures with protozeolites can have desirable effects due to their open structures (Figure a), including the promotion of mesoporous features in synthesis products or the acceleration of crystallization kinetics. , Yu and co-workers demonstrated that ball-milling protozeolites can facilitate the formation of zeolite MFI nanosheets by generating solids with platelike structures where external silanol sites are redistributed in a nonrandom, curvature-dependent fashion with higher probabilities of proximal silanol sites. Local regions with higher densities of silanol sites are more reactive toward crystal growth where a coalescence boundary can develop between the amorphous precursor and the emerging crystalline state (Figure b).…”
Section: Precursors In Zeolite Growth Mediamentioning
confidence: 99%
“…These are often referred to as protozeolites or embryonic zeolites ,, since they possess elements of the zeolite structure but are very small in size with only short-range order (a few nanometers in length). Studies have demonstrated that seeding growth mixtures with protozeolites can have desirable effects due to their open structures (Figure a), including the promotion of mesoporous features in synthesis products or the acceleration of crystallization kinetics. , Yu and co-workers demonstrated that ball-milling protozeolites can facilitate the formation of zeolite MFI nanosheets by generating solids with platelike structures where external silanol sites are redistributed in a nonrandom, curvature-dependent fashion with higher probabilities of proximal silanol sites. Local regions with higher densities of silanol sites are more reactive toward crystal growth where a coalescence boundary can develop between the amorphous precursor and the emerging crystalline state (Figure b).…”
Section: Precursors In Zeolite Growth Mediamentioning
confidence: 99%
“…The protozeolite-seeded strategy can also be applied to synthesize hierarchical ZSM-5 zeolites with high-quality intrapenetrated mesopores and outstanding hydrothermal stabilities. 33 Benefiting from their high pore connectivity, the hierarchical ZSM-5 zeolites with intrapenetrated mesopores exhibited an ultralong lifetime (443.9 h) and a high propylene selectivity (47.92%) in the MTP reaction.…”
Section: Hierarchical Zeolite Catalystsmentioning
confidence: 99%
“…In contrast, the mesoporogen-free methods such as kinetic regulation, , seed-assisted synthesis, and steam-assisted synthesis are promising strategies for the efficient and green construction of hierarchical zeolite structures avoiding the usage of mesopore-generating agents. Through kinetic regulation, hierarchical zeolites can be prepared and modulated by controlling both nucleation and growth processes. , For example, our group developed an amino-acid-assisted kinetic regulation method to produce single-crystalline hierarchical ZSM-5 crystals with a two-step crystallization process.…”
Section: Preparation Strategies For Zeolite-based Catalysts With Hier...mentioning
confidence: 99%
See 2 more Smart Citations